Mangrove Distribution and Estimation of Canopy Closure Condition: Employing the Simple Hemispherical Photography Method within the Mangrove Community of Waiheru Village - Pietersz, Janson Hans; Pentury, Reinhardus (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2023)
The canopy closure within Waiheru Village's mangrove community is crucial in shielding residential areas from robust winds and providing shade for associated aquatic organisms, thereby mitigating the effects of direct sunlight. Furthermore, the shading provided by the mangrove canopy contributes to the area's carrying capacity for developing mangrove-based ecotourism. This study aims to investigate the distribution of mangrove species, substrate distribution, and the condition of the mangrove canopy closure. Stratified Random Sampling was employed for the data collection on mangroves and substrates, while the Hemispherical Photography method was utilized to gather canopy cover data. The analysis revealed the presence of 11 mangrove species from seven different families, with Rhizophora mucronata exhibiting the most extensive growth distribution compared to other species. Two substrate types, sandy and sandy mud, were also identified. The mangrove canopy closure in Waiheru Village remains in favorable condition, as most observation stations demonstrate a high proportion of dense and moderate canopy closure.